2015
DOI: 10.1074/jbc.m115.678508
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Key Residues of ISD11 Critical for NFS1-ISD11 Subcomplex Stability

Abstract: Background: NFS1-ISD11 complex is essential for the Fe-S cluster assembly process and the homozygous R68L ISD11 mutation causes the mitochondrial disorder, COXPD19. Results: Putative helix-3 and the C terminus of ISD11 are critical for NFS1-ISD11 subcomplex formation and Fe-S cluster biogenesis. Conclusion: ISD11 interaction is critical for NFS1 stability and its steady-state levels, in vivo. Significance: Identified important ISD11 residues will provides valuable information to understand COXPD19 progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…As mentioned previously, it was found that NFS1 and ISD11 interact in human mitochondria, suggesting that the last would be required for the assembly of Fe-S proteins [ 38 ]. Moreover, the critical amino acid residues for the interaction have been mapped [ 47 ]. Recently, it was reported the structure of a heterodecamer multiprotein complex that would be key for the biosynthesis of mitochondrial Fe-S clusters in humans containing two copies of each of NFS1, frataxin (FXN), ISCU, ISD11, and ACP [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned previously, it was found that NFS1 and ISD11 interact in human mitochondria, suggesting that the last would be required for the assembly of Fe-S proteins [ 38 ]. Moreover, the critical amino acid residues for the interaction have been mapped [ 47 ]. Recently, it was reported the structure of a heterodecamer multiprotein complex that would be key for the biosynthesis of mitochondrial Fe-S clusters in humans containing two copies of each of NFS1, frataxin (FXN), ISCU, ISD11, and ACP [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…A secondary structure prediction shows that AtISD11 has 2 helix domains close to the N-terminus of the protein and they are well conserved ( Figure 4 A). It was described that Arg68 from human ISD11 is critical for the interaction with NFS1, but also other amino acid residues are involved in ISD11 stabilization of NFS1 such as Phe40 and Leu63 [ 47 ]. We found that Phe40, Leu63, and Arg68 are conserved in AtISD11 (Phe38, Leu61, and Arg66, AtISD11 numbering) ( Figure 4 B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to Escherichia coli ( E. coli ) cysteine desulfurase IscS, NFS1 requires the adaptor protein ISD11 in order to maintain its activity. The NFS1-ISD11 complex is essential for nuclear and mitochondrial iron-sulfur protein biosynthesis, moreover, the homozygous R68L ISD11 mutation causes the mitochondrial genetic disorder COXPD19 [ 6 , 7 ]. However, the homology of the eukaryotic ISD11 protein has not been identified in the prokaryote to date.…”
Section: Introductionmentioning
confidence: 99%